ANALISIS SEKTOR UNGGULAN DI KABUPATEN BANYUWANGI DI MASA PANDEMI DAN NEW NORMAL - Putra, Aldo Lovenka; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
This study analyzes the areas that need to be prioritized for development to promote economic growth in Banyuwangi district. The analysis methods used are location quotient (LQ) analysis, dynamic location quotient (DLQ) analysis, and variable density analysis. Uses PDRB data for GRDP of Banyuwangi  and East Java Province, obtained from the Central Statistics Agency (BPS) website. The results of the analysis concluded that the main priority sectors for development to promote economic growth in Banyuwangi Regency, based on the LQ analysis, are agriculture, forestry and fisheries; Mining and excavation; Construction; and educational services. Underpinned by the DLQ analysis, which points out all potential areas to be developed with the aim of improving the regional economy. At the same time, according to the results of analysis of transfer proportion, some priority sectors are agriculture, forestry and fishery; Processing industry; Construction; Commercial, Hotel and Restaurant; and Information and Communications. Keyword : Environment and Growth, Economic Growth, Microeconomic Policy Klasifikasi JEL: O44, F43, D04